2005
DOI: 10.1016/j.neuroimage.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Classifying spatial patterns of brain activity with machine learning methods: Application to lie detection

Abstract: Patterns of brain activity during deception have recently been characterized with fMRI on the multi-subject average group level. The clinical value of fMRI in lie detection will be determined by the ability to detect deception in individual subjects, rather than group averages. High-dimensional non-linear pattern classification methods applied to functional magnetic resonance (fMRI) images were used to discriminate between the spatial patterns of brain activity associated with lie and truth. In 22 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
256
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 381 publications
(266 citation statements)
references
References 22 publications
3
256
2
5
Order By: Relevance
“…Therefore, detection of this structural pattern can lead to very early diagnosis of prodromal AD. This study adds to mounting evidence in the literature for the importance of pattern classification methods in detecting subtle and complex structural and functional patterns [10,11,21,37].…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, detection of this structural pattern can lead to very early diagnosis of prodromal AD. This study adds to mounting evidence in the literature for the importance of pattern classification methods in detecting subtle and complex structural and functional patterns [10,11,21,37].…”
Section: Introductionmentioning
confidence: 72%
“…We consider the specific choice of classification algorithm to be a modular aspect of our software design, but chose SVM for several reasons. First, SVM has been prevalent in the recent brain-state fMRI literature [Cox and Savoy, 2003;Davatzikos et al, 2005;LaConte et al, 2005c;Mitchell et al, 2004]. In addition, our comparison of SVM with linear discriminant analysis [LaConte et al, 2005c] indicated that SVMs tend to be less sensitive to preprocessing issues, which is highly desirable for realtime applications.…”
Section: Real-time Implementationmentioning
confidence: 91%
“…Consequently, there has been a remarkable surge in cognitive neuroscientific interest and inventive experimental designs focused on classification of brain states from fMRI data. The applications have been broad and include lie detection [Davatzikos et al, 2005], unconsciously perceived sensory stimuli [Haynes and Rees, 2005], behavioral choices in the context of emotional perception [Pessoa and Padmala, 2005], early visual areas [Kamitani and Tong, 2005], information-based mapping [Kriegeskorte et al, 2006], and memory recall [Polyn et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…However, VBM analyses are of limited value for individual diagnosis, since they measure group differences and are not equipped to classify individuals. Towards this goal, high-dimensional pattern classification methods have been pursued in recent years (Davatzikos, 2004;Duchesne et al, 2006;Fan et al, 2006a;Fan et al, 2007a;Fan et al, 2005Fan et al, , 2006bFan et al, 2007b;Lao et al, 2004;Liu et al, 2004;Timoner et al, 2002), and have shown great potential in a variety of neuroimaging studies (Davatzikos et al, in press, 2006;Davatzikos et al, 2005a;Davatzikos et al, 2005b;Fan et al, 2008a;Fan et al, 2005Fan et al, , 2006bFan et al, 2007b;Kawasaki et al, 2007;Mourao-Miranda et al, 2005;Yoon et al, 2007). Unlike VBM-type methods, which are mass univariate and don't consider statistical associations among different brain regions, high-dimensional pattern classification methods are multivariate, thereby leading to better group separation, which is critical for individual diagnosis.…”
Section: Introductionmentioning
confidence: 99%